2018
DOI: 10.1093/icb/icy066
|View full text |Cite
|
Sign up to set email alerts
|

Behavior, Electrophysiology, and Robotics Experiments to Study Lateral Line Sensing in Fishes

Abstract: The lateral line system is a sensory system unique to fishes and amphibians. It is composed of distributed mechanosensory hair cell organs on the head and body (neuromasts), which are sensitive to pressure gradients and water movements. Over the last decade, we have pursued an interdisciplinary approach by combining behavioral, electrophysiology, and robotics experiments to study this fascinating sensory system. In behavioral and electrophysiology experiments, we have studied the larval lateral line system in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 88 publications
0
9
0
Order By: Relevance
“…To this end, we used several parameters of nervous-system structure and function by combining sarm1 hzm13 with transgenes expressing fluorescent markers in the sensory neurons of the mechanosensory lateral line, as well as in their associated Schwann cells 46,47 . The lateralline system is ideal for such in vivo studies under normal and altered conditions [48][49][50][51] . It combines the organization of a typical vertebrate sensory system with the amenability for controlled experimental interventions that include microsurgery, pharmacology, and optogenetics 41,42,52,53 .…”
Section: Identification and Mutagenesis Of Sarm1 In Zebrafishmentioning
confidence: 99%
“…To this end, we used several parameters of nervous-system structure and function by combining sarm1 hzm13 with transgenes expressing fluorescent markers in the sensory neurons of the mechanosensory lateral line, as well as in their associated Schwann cells 46,47 . The lateralline system is ideal for such in vivo studies under normal and altered conditions [48][49][50][51] . It combines the organization of a typical vertebrate sensory system with the amenability for controlled experimental interventions that include microsurgery, pharmacology, and optogenetics 41,42,52,53 .…”
Section: Identification and Mutagenesis Of Sarm1 In Zebrafishmentioning
confidence: 99%
“…There is a long and narrow sideline system on the surface of a fish's body, which not only regulates swimming behavior in real time by sensing the flow velocity, direction, and pressure, but also has many important sensory functions, such as hearing and touch, which plays a role in finding bait, migration, clustering, reproduction, defense, and other life processes. [152,153] In recent years, researchers have made good progress through the bionic sideline system. [154][155][156][157] In addition, the integration of flexible sensing and soft actuating is also an important part of realizing intelligent control for soft robots.…”
Section: Discussionmentioning
confidence: 99%
“…In terms of LL efferents, it has been shown that both cholinergic and dopaminergic efferent neurons modulate the hair-cell output (Haehnel-Taguchi M, Akanyeti O and Liao JC, 2018). In stages 48-55 tadpoles, the efferent activity was shown to be corollary to the locomotor rhythms, in phase with ipsilateral spinal central pattern generator activity and suppressing afferent sensory signalling (Chagnaud BP et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Aquatic vertebrates including fish and Anura use the distributed mechanosensory lateral line (LL) system to sense hydrodynamic disturbances (Bleckmann H and Zelick R, 2009; Coombs S and Zaidi ZH, 2012; Kroese AB et al, 1978; Montgomery JC et al, 1997; Stewart WJ et al, 2013). The LL system provides an important sensory mode for animals to conduct rheotaxis (facing into and swimming against a current) (Akanyeti O et al, 2016; Haehnel-Taguchi M et al, 2018; Montgomery JC, Baker CF and Carton AG, 1997; Oteiza P et al, 2017; Simmons AM et al, 2004), predator avoidance and escape (McHenry MJ et al, 2009; Roberts A et al, 2009; Stewart WJ, Cardenas GS and McHenry MJ, 2013) and prey detection (Claas B and Munz H, 1996; Nagiel A et al, 2008). There are three types of LL receptor: mechanosensory neuromasts, pit organs (Northcutt RG, 1992) and electroreceptive ampullary organs.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation